A conceptual framework for the assessment of multiple functions of agro-ecosystems: a case study of Trás-os-Montes olive groves - Fleskens, Luuk (2009)
Multifunctionality in agriculture has received a lot of attention the last decade from researchers and policy-makers alike, perhaps most notably evidenced by the important changes made to the EU’s Common Agricultural Policy. While the concept has been embraced by environmentalists envisioning positive impulses for decoupling and a range of local stakeholders recognizing implicit marketing opportunities involved, it has also been criticized as a mere argument in favour of disguised protectionism. Problematic in this discussion is the lack of an operationalising framework for the assessment of multiple functions. In this paper, we discuss such a framework and the role it can play in the decisionmaking process. Focusing on a case study about olive farming on sloping and mountainous land in northeastern Portugal, the contribution discusses methods for studying multiple functions of agroecosystems. While function assessment is presented from a research perspective, its relevance for stakeholders is also stressed here. By using the metaphor of a house, the method could appeal to a wide range of actors. In the case study, we conclude that olive groves on sloping and mountainous land particularly fall short in supplying ecological functions. They do however contribute significantly to the local economy, generate employment and perform an important role in maintaining the cultural landscape and identity, and are thus vital to regional development and to stop outmigration of the population. Policy-makers could use the function assessment tool to design effective cross-compliance rules and relevant agro-environmental measures to reinforce ecological and social functions, and to communicate ideas to other stakeholders. As such, it provides an extension of public debate and can reinforce decision-making by visualizing trends, development alternatives or scenarios. The role of research in this method is to facilitate dialogue between stakeholder groups and to feed the process with relevant indicators